#TITLE_ALTERNATIVE# - SETIAWAN (NIM : 15110021) ; Pembimbing : Dr. Ir. Kosasih Prijatna, M.Sc, GUNTUR
Earthquakes are common in Sumatra island because the island is located at the convergent boundary where Sunda Plate is subducted under the Indo - Australian plate . One earthquake was an earthquake that occurred in Aceh in 2013 with a strength of 6.2 M . Earthquake on July 2, this occurs at a depth of 10 kilometers with its epicenter near the northwest tip of Sumatra , about 55 kilometers south of Bireun . It is necessary for deformation monitoring in the area affected so that the earthquake disaster mitigation actions that can be performed maximally. To investigate the deformation that occurred in the region of Aceh earthquake 2013, so it made the episodic GPS observations that happened in two period, July dan December 2013 . GPS data is then processed to obtain the geodetic dan geocentric coordinates dan standard deviation of each point . The results of the geocentrik coordinate then transformed into the topocentrik coordinate , showed a shift ranging from 1 mm - 20 mm towards the east . It also calculated the strain on the region, dan we got the result of compression is 8.6698246 μstrain. The results still need to be done next GPS observations , because the results obtained only from two observations with an interval less than one year , then it is possible that the data obtained are outliers .